2022
DOI: 10.1038/s41598-022-11623-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of anti-PF4 IgG after AZD1222 (ChAdOx1 nCoV-19) vaccination

Abstract: Rare cases of thrombosis with thrombocytopenia syndrome (TTS) have been reported after AZD1222. Anti-platelet factor-4 (PF4) antibodies were observed in patients following presentation of TTS, however it is unclear if AZD1222 was responsible for inducing production of anti-PF4. Paired samples (baseline and day-15) from a phase 3 trial of AZD1222 vs placebo were analyzed for anti-PF4 levels; 19/1727 (1.1%, AZD1222) vs 7/857 (0.8%, placebo) participants were anti-PF4-IgG-negative at baseline but had moderate Day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…Consequently, we conducted a comparative discussion based on the aforementioned relevant literature. As per a study funded by AstraZeneca and the US Government, HDs with a male predominance (60.3%) and young adults' predominance (≥18 and <56 years old, 51.0%) did not exhibit statistically significant elevation of anti‐HPF4 after one shot of AZ vaccine 33,34 . However, our study also identified an increase in anti‐PF4 in some individuals (75.68%, 28 in 37) who received two adenoviral vector vaccines without clinical VITT.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Consequently, we conducted a comparative discussion based on the aforementioned relevant literature. As per a study funded by AstraZeneca and the US Government, HDs with a male predominance (60.3%) and young adults' predominance (≥18 and <56 years old, 51.0%) did not exhibit statistically significant elevation of anti‐HPF4 after one shot of AZ vaccine 33,34 . However, our study also identified an increase in anti‐PF4 in some individuals (75.68%, 28 in 37) who received two adenoviral vector vaccines without clinical VITT.…”
Section: Discussionsupporting
confidence: 70%
“…Government, HDs with a male predominance (60.3%) and young adults' predominance (≥18 and <56 years old, 51.0%) did not exhibit statistically significant elevation of anti-HPF4 after one shot of AZ vaccine. 33,34 However, our study also identified an increase in anti-PF4 in some individuals (75.68%, 28 in 37) who received two adenoviral vector vaccines without clinical VITT. Furthermore, an increase in anti-HPF4 (43.24%, 16 in 37) was observed in HDs after receiving an mRNA booster in our cohort.…”
Section: Association Of Higher Cith3 Levels With Rash But Not Fever O...mentioning
confidence: 51%
“…The presence of low level anti-PF4 antibodies and platelet activation does not predict the induction of TTS. Indeed 1-2% of individuals are positive for low levels of anti-PF4 IgG and these individuals do not develop TTS post-vaccination 32,33 . Also, vaccination with Vaxzevria does not generally increase anti-PF4 levels in healthy vaccine recipients who did not develop VITT 32 .…”
Section: Understanding the Biological Mechanisms And Impact Of Vaccin...mentioning
confidence: 99%
“…Indeed 1-2% of individuals are positive for low levels of anti-PF4 IgG and these individuals do not develop TTS post-vaccination 32,33 . Also, vaccination with Vaxzevria does not generally increase anti-PF4 levels in healthy vaccine recipients who did not develop VITT 32 . According to the company's working hypothesis, the nature of the individual host response determines whether TTS is induced upon exposure to the ChAdOx1-PF4 complex.…”
Section: Understanding the Biological Mechanisms And Impact Of Vaccin...mentioning
confidence: 99%
“…Moreover, a post-hoc analysis of sera from subjects recruited in a phase 3 trial of ChAdOx1-SARS-COV-2 vaccine found no increased rate of detection of anti-PF4 IgG post-vaccination compared to placebo during the period of highest TTS risk. Indeed, 19/1727 (1.1%, ChA-dOx1) vs 7/857 (0.8%, placebo) participants were anti-PF4-IgGnegative at baseline, but had moderate Day-15 levels (P = 0.676) and 0/35 and 1/20 (5.0%) had moderate levels at baseline but high Day-15 levels [54]. None of the participants to the trial experienced VITT following administration of vaccine or placebo.…”
Section: The Core Question: Why Me?mentioning
confidence: 98%